2017
DOI: 10.2209/tdcpublication.2016-0029
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Temporal Change in Free Flap Volume after Tongue Reconstruction

Abstract: The purpose of this study was to investigate three-dimensionally temporal change in flap volume after free flap reconstructive surgery in tongue cancer patients. The results revealed an average change in flap volume of 82.3% at 1 year postoperatively. Change in tongue volume at approximately 6 months postoperatively showed a correlation with triglyceride levels. A correlation was also found between albumin levels and tongue volume at 1 year onwards postoperatively. The goal of such surgery in patients with ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…No significant difference was found in preoperative BMI between those with increased and decreased RTFV, consistent with a previous study's findings 15 . The study also found correlation between RTFV change at 6 months postoperative and preoperative triglyceride levels.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…No significant difference was found in preoperative BMI between those with increased and decreased RTFV, consistent with a previous study's findings 15 . The study also found correlation between RTFV change at 6 months postoperative and preoperative triglyceride levels.…”
Section: Discussionsupporting
confidence: 91%
“…Within 6 months postoperatively, high preoperative triglyceride levels led to a smaller decrease in RTFV, suggesting that RTFV is influenced by the patient's fat percentage. After postoperative 1 year, high preoperative albumin levels led to smaller decrease in RTFV, which suggested that preoperative nutritional status affects RTFV 15 . BMI, triglyceride, and albumin are all nutritional indices.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, it is difficult to judge the volume change solely from a photograph. Therefore, most recent studies related to flap volume after head and neck reconstruction have used measurement software 3,7,11–13 . To the best of our knowledge, however, this is the first study targeting only the hemi-tongue reconstruction group.…”
Section: Discussionmentioning
confidence: 99%